2017
DOI: 10.1007/s11845-017-1566-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes following spinal fracture in patients with ankylosing spondylitis

Abstract: Patients with ankylosing spondylitis are at risk of spinal fracture and associated spinal cord injury after relatively minor trauma. Delayed diagnosis places the patient at risk of neurological compromise, and thus a high index of suspicion is needed when assessing this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Previous studies have found a very high complication and mortality rate in ASD patients treated surgically [ 22 , 23 ]. In our series, all of the patients had at least one postoperative complication, but only one patient died in the immediate postoperative period from respiratory complications.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found a very high complication and mortality rate in ASD patients treated surgically [ 22 , 23 ]. In our series, all of the patients had at least one postoperative complication, but only one patient died in the immediate postoperative period from respiratory complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, the surgical trauma is significant and there are more postoperative complications [9]. Nugent et al [28] and Nakao et al [22] reported surgical complications with incidences of 64% and 30.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…6 Late diagnosis is the result of misinterpretation of the clinical symptoms by physicians (doctor's delay) as well as by patients (patient's delay). 7 If the patient's delay is understandable, and could be prevented through better education once ASD is diagnosed, 8 doctor's delay is alarming, considering that it is accountable for two-thirds of the overall deferment. There is a lack of definite guidelines.…”
Section: Discussionmentioning
confidence: 99%